Seroprevalence of hepatitis B, hepatitis C and HIV infection among patients undergoing haemodialysis in Buenos Aires, Argentina. Issue 1 (12th January 2021) - Pereson, Matías J.; Martínez, Alfredo P.; Isaac, Katia; Laham, Gustavo; Ridruejo, Ezequiel; Garcia, Gabriel H.; Flichman, Diego M.; Di Lello, Federico A.
Abstract : Introduction. Blood-borne infections are a major cause of harm in individuals on haemodialysis (HD). In particular, knowledge about hepatitis B (HBV), hepatitis C (HCV) and human immunodeficiency virus (HIV) status in HD patients is a major concern, since these infections may cause comorbidities in this setting. There is a paucity of data regarding this issue in Argentina. Hypothesis/Gap Statement. The epidemiological surveillance of HBV, HCV, and HIV is a fundamental tool for planning and implementing health strategies in order to prevent and control viral transmission of these viral agents. Aim. To determine the seroprevalence of HBV, HCV and HIV infections in HD patients in Buenos Aires, Argentina. Methodology. Seven hundred and forty-eight HD patients were included in a retrospective cross-sectional study. Serological assays were performed to determine HBV, HCV and HIV status. HBV HBsAg and anti-HBc IgG were analysed using AxSYM (samples before 2010) or the Architect Abbott system (samples since 2010), anti-HCV IgG testing was performed using the anti-HCV enzyme immunoassay AxSYM HCV V3.0 and ARCHITECT anti-HCV, while HIV was tested for using AxSYM HIV 1/2 gO and ARCHITECT HIV Ag/Ab Combination. HCV genotyping was carried out by phylogenetic analysis of the NS5B partial gene. Results. Infection with one of the viruses was detected in 31.1 % of patients [HBV in 82 (11.0 %), HCV in 179 (23.9 %) and HIV in 6 (0.8 %)]. Thirty-two (4.3 %) patients had 2 virus markers [27 (3.6 %) with HCV/HBV, 4 (0.5 %) with HCV/HIV and 1 (0.13 %) with HBV/HIV]. Finally, a single patient (0.13 %) presented all three markers. Time on dialysis was correlated with HCV but not with HBV infection. The HCV subtype distribution in HD patients was inverted with respect to that observed in the general population (HCV-1a 73.2 % and HCV-1b 26.8 % in HD vs HCV-1a 26.5 % and HCV-1b 73.5 % in the general population, P <0.001). Conclusion. Despite the implementation of universal precautionary biosafety standards for dialysis, infection with HBV and HCV continues to occur at very high rates in HD patients. The results emphasize the need to carry out proactive tasks for early diagnosis and treatment of infected individuals and to vaccinate those with non-protective antiHBs antibodies in order to reduce morbidity and mortality in HD patients.